Penerapan Asas Kebebasan Berkontrak Dalam Perjanjian Sewa Menyewa Rusunawa Antara Warga Terdampak Penggusuran Dengan Pemprov DKI Jakarta (Studi Kasus Warga Terdampak Penggusuran Yang Menghuni Rusunawa Rawa Bebek) - Azzahra, Marcella; Wahyuni, Ridha (Media Hukum Indonesia (MHI), 2024)
This research aims to analyse the application of the principle of freedom of contract in the lease agreement between residents affected by eviction and explain the legal steps that can be taken by residents affected by eviction from potential eviction again. This research uses Empirical Juridical method and approach in the form of analytical descriptive using case approach. Based on the results of the research, the principle of freedom of contract is the principle of the parties in making agreements. However, the application of this principle is not reflected in the residents affected by the eviction of the Ciliwung river who were relocated to the Rawa Bebek flat. Residents must occupy it using the lease method. This action is not based on the principle of freedom of contract so that the affected residents are forced to agree to the contents of the agreement. If seen from the perspective of residents affected by the eviction, the principle of freedom of contract does not exist in the implementation of the lease agreement. Legal steps that can be taken are non-litigation efforts such as mediation, negotiation and also litigation efforts through the court.